Black and White Differences in Cognitive Function Test Scores: What Explains the Difference? - Mehta, Kala M. (2004)
Several studies have reported that older black and Latino adults have lower cognitive function test scores than older white adults, but few have comprehensively examined reasons for score differences. This study evaluates whether differences in health and socioeconomic indicators, including literacy level, can explain differences in cognitive function test scores between older black and white adults.